2020
DOI: 10.3390/jrfm13040070
|View full text |Cite
|
Sign up to set email alerts
|

Oil Price, Oil Price Implied Volatility (OVX) and Illiquidity Premiums in the US: (A)symmetry and the Impact of Macroeconomic Factors

Abstract: We examine the impact of oil price and oil price volatility on US illiquidity premiums (return on illiquid-minus-liquid stocks), using the US Oil Fund options implied volatility OVX index. We use daily data from 2007 to 2018, taking into account the structural break in June 2009 and controlling for macroeconomic factors. Both OLS and VAR models indicate that oil price has a significantly positive impact and OVX has a significantly negative impact on premiums, for the full sample and post-crisis period. These r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 87 publications
(155 reference statements)
0
0
0
Order By: Relevance
“…Adhikari Sudip and Khanal Aditya R. found that the perceived higher commercial risks significantly increased the debt use, savings use, and debt-to-equity ratio of small farmers (Skadina & Veinbergs, 2021). In addition, the research results indicate that factors such as the age and education level of operators, family participation, income, land area, alternative solutions adopted by farm enterprises, and farmers' continuation plans have a significant impact on the financing decisions of small-scale farm operations (Essa & Giouvris, 2020). The original/value author investigated an important empirical question, examining the risk-balancing behavior of small farm operations in the United States.…”
Section: Possible Impacts Of Commercial Risksmentioning
confidence: 85%
“…Adhikari Sudip and Khanal Aditya R. found that the perceived higher commercial risks significantly increased the debt use, savings use, and debt-to-equity ratio of small farmers (Skadina & Veinbergs, 2021). In addition, the research results indicate that factors such as the age and education level of operators, family participation, income, land area, alternative solutions adopted by farm enterprises, and farmers' continuation plans have a significant impact on the financing decisions of small-scale farm operations (Essa & Giouvris, 2020). The original/value author investigated an important empirical question, examining the risk-balancing behavior of small farm operations in the United States.…”
Section: Possible Impacts Of Commercial Risksmentioning
confidence: 85%